Поняття безпеки дорожнього руху як об'єкта адміністративно-правового регулювання - Чанцева, А. О.; Chantseva, A. O. (Європейські перспективи. - 2022. - № 2. – С. 199-205, 2022)
Надано комплексне і всеохоплююче визначення поняття безпеки дорожнього руху. Встановлено характерні складові елементи цього поняття та його чинне місце у сучасній системі адміністративного права України.

In this article, the key elements of the current state of the process of defi ning the concept of road traffi c safety as an object of administrative and legal regulation are investigated and thoroughly analyzed. Also, ways of possible improvement of the state of the conceptual apparatus and classifying tools of the system of administrative law of Ukraine regarding the proper observance of safety in modern conditions of road traffi c functioning are considered. It is noted that various domestic and foreign jurists, at their own discretion, tend to interpret the essence and important elements of the concept of road traffi c safety, which exists in the system of concepts of administrative law today. Therefore, in this article, an attempt is made to provide a comprehensive and comprehensive defi nition of road safety as an object of administrative and legal regulation and to establish its characteristic features.

Дано комплексное и всеобъемлющее определение понятия безопасности дорожного движения. Установлены характерные составляющие этого понятия и его действующее место в современной системе административного права Украины.
Чанцева, А. О. Поняття безпеки дорожнього руху як об'єкта адміністративно-правового регулювання / Чанцева Анна Олександрівна // Європейські перспективи. - 2022. - № 2. – С. 199-205. - DOI: 10.32782/EP.2022.2.30.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; безпека дорожнього руху; road safety; безопасность дорожного движения; адміністративно-правове регулювання; administrative and legal regulation; административно-правовое регулирование; державна політика; state policy; государственная политика; погляди вчених; views of scientists; взгляды ученых